SUBTITUSI TEPUNG TERIGU DENGAN TEPUNG KELADI TERMODIFIKASI DALAM PEMBUATAN BISKUIT - Lero, Nikodemus Jawu; Ahmadi, Kgs; Wirawan, Wirawan (Fakultas Pertanian, 2019)
The use of taro as food is still very limited even though its potential is very broad. One of the efforts to utilize taro flour is through the use of flour as material for making biscuit. The purpose of this study was to get the proportion of wheat flour with modified taro flour in making biscuits. The experimental design used was a completely randomized design with one factor consisting of p1=substitution of flour with 20% modified taro flour, p2 substitution of wheat flour with 40% modified fluor, p3= substitution of wheat flour with 60% modified taro flour and p4= substitution of wheat flour with 80% modified taro flour. Each treatment was repeated 5 times. The research showed that in making biscuits with a combination of 80% wheat flour and 20% taro flour was the best treatment with a protein content of 7.17%, water content 4.62%, ash content 2.04%, and hardness 10.6N, preference 3.3 color (liked), Taste preference 3.4 (liked), aroma preference 3.35 (liked), and preference texture 3.65 (liked). The business feasibility analysis for the manufacture of wheat flour and taro flour in the manufacture of biscuits is feasible in the household scale due to its HPP is 15,278.49 /packaging. The packaging selling price is 17,570.27. The net profit per day obtained is IDR. 29793.06 and the BEP unit is 2,276.39, the BEP price is IDR 39,996,753.82 and the RCR is 1.15. Penggunaan keladi sebagai bahan pangan masih sangat terbatas padahal potensinya sangat luas. Salah satu upaya untuk memanfaatkan tepung keladi adalah melalui penggunaan tepung sebagai bahan untuk pembuatan biskuit. Tujuan penelitian ini yaitu untuk mendapatkan proporsi tepung terigu dengan tepung keladi termodifikasi dalam pembuatan biskuit. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap dengan satu faktor yang terdiri dari P1 = Substitusi tepung terigu dengan 20% tepungkeladi termodifikasi, P2 = Substitusi tepung terigu dengan 40% tepung termodifikasi, P3 = Substitusi tepung terigu dengan 60% tepung keladi termodifikasi, P4= Substitusi tepung terigu dengan 80% tepung keladi termodifikasi. Setiap perlakuan di ulang sebanyak 5 kali. Hasil penelitian menunjukan bahwa pembuatan biskuit dengan kombinasi tepung terigu 80% dan tepung keladi 20% merupakan perlakuan terbaik dengan kadar protein 7,17%, kadar Air 4,62 %, Kadar Abu 2,04 %, dan Daya Patah 10,6N, kesukaan warna 3,3 (suka), kesukaan Rasa 3,4 (suka), kesukaan Aroma 3,35 (suka), dan kesukaan Tekstur 3,65 (suka). Analisis kelayakan usaha untuk pembuatan subtitusi tepung terigu dan tepung keladi dalam pembuatan biskuit layak diusahakan dalam skala rumah tangga karena HPP 15.278,49 /kemasan. Harga jual perkemasan 17.570,27. Keuntungan bersih per hari yang diperoleh adalah Rp 29793.06dan BEPunit sebesar 2.276,39, BEP harga sebesar Rp 39.996.753,82 dan RCR sebesar 1,15.